Portrayal of the American Culture through Metafiction - BABAEI, ABDOLRAZAGH; TAADOLKHAH, AMIN (Journal of Education Culture and Society, 2020)
Kurt Vonnegut’s position that artists should be treasured as alarm systems and as biological agents of change comes most pertinent in his two great novels. The selected English novels of the past century – Cat’s Cradle (1963), Slaughterhouse Five (1969), and Breakfast of Champions (1973) – connect the world of fiction to the harsh realities of the world via creative metafictional strategies, making literature an alarm coated with the comforting lies of storytelling. It is metafi ction that enables Vonnegut to create different understandings of historical events by writing a kind of literature that combines facts and fiction. Defi ned as a kind of narrative that “self-consciously and systematically draws attention to its status as artefact” metafiction stands against the duplicitous “suspension of disbelief” that is simply an imitation and interpretation of presumed realities. As a postmodern mode of writing it opts for an undisguised narration that undermines not only the author’s univocal control over fiction but also challenges the established understanding of the ideas. Multidimensional display of events and thoughts by Vonnegut works in direction of metafiction to give readers a self-conscious awareness of what they read. Hiroshima bombing in 1946 and the destruction of Dresden in Germany by allied forces in World War II are the subjects of the selected novels respectively. In them Vonnegut presents a creative account in the form of playful fictions. The study aims to investigate how the novelist portrayed human mentality of the American culture by telling self-referential stories that focus on two historical events and some prevailing cultural problems.